PERAN USTADZ DAN USTAZAH DALAM PEMBINAAN PROGRAM TAHSIN DI TPA RAUDHATUL QUR’AN LHOKNGA - Tami Syahputra (Yayasan An-Nur Meunara Baro, 2025)
Ustadz/ah plays an important role in Islamic religious learning at TPA Raudhatul Qur'an Lhoknga Aceh Besar, including guiding, directing and forming the character of the students. This research examines the role of ustadz/ah in developing Al-Qur'an tahsin programs with three focuses: 1) The process of developing Al-Qur'an reading, 2) Obstacles faced, and 3) Solutions to these obstacles. Descriptive qualitative methods were used with observation, interviews and documentation. The research results show that tahsin coaching is carried out optimally through various methods, media and technology. Obstacles faced include the absence of students due to activities outside the TPA and differences in understanding in the pronunciation of makhrijul letters. The solutions implemented include training for ustadz/ah and dividing groups of students based on ability. These findings emphasize the crucial role of ustadz/ah in the success of the tahsin program at TPA Raudhatul Qur'an.